FRI0288 Baseline characteristics of newly diagnosed patients with axial spondyloarthritis: First results from the giant cohort. (23rd January 2014) - Van Praet, L.; Carron, P.; Elewaut, D.; van den Bosch, F.
Abstract : Background: Recently, the field of spondyloarthritis (SpA) has experienced major developments, among them the possibility of earlier diagnosis, particularly by the introduction of MRI of the sacroiliac joints. The application of the new ASAS classification criteria for axial SpA (1) has allowed to define a broader spectrum of SpA patients, ranging from non-radiographic axial SpA (nr-axSpA) to classic ankylosing spondylitis (AS) according to modified New York criteria. Objectives: The present study describes the baseline characteristics of axial SpA patients presenting for the first time in our department. Methods: The Gent Inflammatory Arthritis and spoNdylitis cohorT (GIANT) is an observational cohort in which patients with axial and peripheral SpA according to the ASAS criteria are prospectively followed; at present 110 patients have been included. Results: Baseline characteristics of 46 newly diagnosed patients with axial SpA are reported (22 men, 24 women). Symptom duration varied from 0 to 23 years (median: 2.3 years). Mean age was 33.5 years. All patients were suffering from chronic back pain which started before the age of 45 years; inflammatory back pain, defined by ASAS criteria, was present in 78%. Seventy-six percent of the patients were HLA-B27 positive and active inflammatory lesions on MRI were found in 91.9%. Twenty-eight percent of the patients showed definite radiographic sacroiliitis according to Modified New York criteria at first presentation. Twenty-six percent of the patients were active smokers. Symptom duration was comparable between the nr-axSpA and the AS group. The male/female ratio was slightly higher in AS versus nr-axSpA. Extra-articular manifestations and HLA-B27 positivity were equally present in both groups. Inflammatory parameters were higher in the AS group. Conclusions: A surprisingly high frequency of AS was found in newly diagnosed patients with axial SpA with a comparable symptom duration. Men and women were equally affected. The prevalence of extra-articular manifestations was similar between nr-axSpA and established AS. References: Sieper J, Rudwaleit M, Baraliakos X, et al. The Assessment of SpondyloArthritis international Society (ASAS) handbook: a guide to assess spondyloarthritis. Ann Rheum Dis 2009;68(Suppl 2):ii1-ii44. Disclosure of Interest: None Declared